Influence of rapid thermal oxidation process on the optoelectronic characteristics of PSI devices - Alwan, M. Alwan; Narges, Z. Abdulzahra; Naser Mahmoud, Ahmed; Halim, N.H.A. (Universiti Malaysia Perlis, 2009)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1 ; issue 1, 2008 & vol. 2 ; issue 1 & 2, 2009.